2016
DOI: 10.1039/c6an00402d
|View full text |Cite
|
Sign up to set email alerts
|

Pencil it in: pencil drawn electrochemical sensing platforms

Abstract: Inspired by recent reports concerning the utilisation of hand drawn pencil macroelectrodes (PDEs), we report the fabrication, characterisation (physicochemical and electrochemical) and implementation (electrochemical sensing) of various PDEs drawn upon a flexible polyester substrate. Electrochemical characterisation reveals that there are no quantifiable electrochemical responses upon utilising these PDEs with an electroactive analyte that requires an electrochemical oxidation step first, therefore the PDEs ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 39 publications
1
31
0
3
Order By: Relevance
“…The typical scale of the electrodes presented here is in the mm to cm range. This is in agreement with some of the devices presented in the literature, and is consistent with sizes compatible with tabletop fabrication methods …”
Section: Resultssupporting
confidence: 92%
“…The typical scale of the electrodes presented here is in the mm to cm range. This is in agreement with some of the devices presented in the literature, and is consistent with sizes compatible with tabletop fabrication methods …”
Section: Resultssupporting
confidence: 92%
“…In recent years, graphite pencils were used for the development of interesting electronic applications like bilayer chemiresistor [ 217 ], photoconductive PbS photodetector realized by pencil graphite electrodes drawn on stone paper acting as substrate, or a hand drawn pencil electrode for determination of lead traces in water [ 73 ], dopamine [ 74 ], or p-nitrophenol [ 30 ]. It was demonstrated that pencil drawn electrodes present the best reversibility and the highest signal if they were drawn 10 times with a 6B pencil [ 75 ]. Doped pencil leads for paper based analytical devices with chemical modified electrodes have been also reported [ 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…More recently, pencil drawn electrodes (PDEs) prepared via mechanical abrasion of graphite on solid substrate have been developed and used as voltammetric sensors for the detection of metal ions. [36][37][38] They offered very water by capillary action in paper is identified as an important advantage in designing microfluidic devices. However, the same phenomenon may lead to potential instability in ISEsdiffused water is absorbed by the paper and transported towards the connectors.…”
Section: -15mentioning
confidence: 99%